The Utility of Physical Activity Micro-Grants: The ParticipACTION Teen Challenge Program. Issue 2 (March 2018) - Ramanathan, Subha; White, Lauren; Luciani, Alicia; Berry, Tanya R.; Deshpande, Sameer; Latimer-Cheung, Amy E.; O'Reilly, Norm; Rhodes, Ryan E.; Spence, John C.; Faulkner, Guy
Youth physical activity levels remain low in Canada and worldwide. Lack of environmental resources (e.g., access to equipment and facilities, transportation options, and participation costs) is a key barrier for youth participation. Micro-grants are small budgets of money awarded via grant applications and may help community organizations facilitate youth physical activity participation by alleviating environmental resource barriers. ParticipACTION Teen Challenge was a national micro-grant scheme administered in Canada. Secondary analysis of survey data from Provincial and Territorial coordinators, registered community organizers, and successful grant applicants were used to evaluate the process and outcomes of Teen Challenge. Results showed that the financial subsidy of 500CAD was used mainly toward equipment, instruction, and transportation. Coordinators and community organizers indicated high levels of satisfaction and benefits for communities and teens. A key benefit for coordinators was leveraging the Teen Challenge network for physical activity promotion. Reported benefits for teenaged participants included leadership opportunities (e.g., helping create and implement programs) and increased physical activity participation. Findings highlight the value of micro-grants for supporting sport and physical activity opportunities for Canadian teens, and show that such schemes address barriers related to environmental resources. The sustainability of micro-grant schemes remains to be seen.